Gender and creative labour (Wiley-Blackwell, 2015)
Introduction – Sexism, segregation and gender roles – Flexibility and informality – Image-making and representation – Boundary-crossing – Notes on contributors
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Cultural industries; Sex discrimination in employment